PENGARUH PEMBERIAN MAKANAN PENDAMPING ASI (MP ASI) DINI DENGAN KEJADIAN STUNTING PADA BALITA USIA 12- 60 BULAN DI POSYANDU BALITA - Mertisa Klevina; Irmawati Mathar (PROFESSIONAL HEALTH JOURNAL, 2023)
ABSTRACT The nutritional problem that occurs in Indonesia is stunting. Stunting is growth failure characterized by low and normal height according to the age of the toddler which is caused by lack of nutritional intake, health status, exclusive breastfeeding, age at which MPASI is given, birth weight, mother's education and economic status. It is feared that toddlers who are stunted will experience growth and development problems, both short and long term. The aim of this research was to determine the relationship between birth weight and early provision of complementary breast milk (MPASI) with the incidence of stunting in toddlers at the toddler posyandu in Genilangit Village, Poncol District, Magetan Regency. The research design used is correlational analytic with a cross sectional approach. The research sample was 67 respondents using the Proportional Random Sampling technique. Data were collected using KIA books, questionnaires and observation sheets, data were analyzed using the Chi-Square Test with a significance level of α = 0.05. The results of research on giving early MPASI showed that the majority of toddlers who were given early MPASI were stunted, 15 respondents (22.4%) and the majority of toddlers who were given MPASI at the right age were not stunted, 39 respondents (58.2%). The analysis results obtained for birth weight were p-value = 0.001 < α = 0.05. Meanwhile, the results of the analysis for giving early MPASI showed a p-value = 0.000 < α = 0.05. Early provision of complementary breast milk (MPASI) is closely related to the incidence of stunting in toddlers. Normal birth weight and giving MPASI at the right age is good for the growth and development of toddlers and has a very low risk of toddlers experiencing stunting. Thus, it is hoped that mothers will pay more attention to nutrition before pregnancy and during pregnancy which is related to the birth weight of toddlers. As well as providing age-appropriate complementary foods for breast milk (MPASI), namely at 6 months of age. Key words: birth weight, early provision of MP-ASI, stunting ABSTRAK Permasalahan gizi yang terjadi di Indonesia adalah stunting. Stunting adalah kegagalan pertumbuhan ditandai dengan tinggi badan kurang dan normal sesuai dengan usia balita yang disebabkan karena kurangnya asupan gizi, status kesehatan, ASI eksklusif, usia pemberian MPASI, berat badan lahir, pendidikan ibu dan status ekonomi. Balita yang stunting dikhawatirkan akan mengalami gangguan tumbuh kembang baik jangka pendek maupun jangka panjang. Tujuan penelitian ini adalah untuk mengetahui hubungan berat badan lahir dan pemberian makanan pendamping ASI (MPASI) dini dengan kejadian stunting pada balita di posyandu balita Desa Genilangit Kecamatan Poncol Kabupaten Magetan. Desain penelitian yang digunakan adalah analitik korelasional dengan pendekatan Cross Sectional. Sampel penelitian sejumlah 67 responden dengan menggunakan teknik Proposional Random Sampling. Pengumpulan data menggunakan buku KIA, kuesioner dan lembar observasi, data dianalisa dengan Uji Chi-Square dengan tingkat signifikansi α =0.05. Hasil penelitian pemberian MPASI dini didapatkan sebagian besar balita yang diberikan MPASI dini mengalami stunting 15 responden (22,4%) dan sebagian besar balita yang diberikan MPASI tepat usia tidak stunting 39 responden (58,2%). Hasil analisa yang didapatkan untuk berat badan lahir nilai p-value =0,001 < α = 0,05. Sedangkan hasil analisa untuk pemberian MPASI dini didapatkan nilai p-value =0,000 < α = 0,05. Pemberian makanan pendamping ASI (MPASI) dini sangat berkaitan dengan kejadian stunting pada balita. Berat badan lahir normal dan pemberian MPASI tepat usia baik untuk tumbuh kembang balita dan sangat rendah resiko balita mengalami stunting. Dengan demikian diharapkan untuk ibu lebih memperhatikan nutrisi sebelum kehamilan dan selama kehamilan yang berkaitan dengan berat lahir balita. Serta memberikan makanan pendamping ASI (MPASI) tepat usia yaitu saat usia 6 bulan. Kata kunci :berat badan lahir, pemberian MP-ASI dini, stunting